Reopening borders to revive the economy and resume travel in Asia and the Pacific health-focused policy recommendations. - Osewe, Patrick L.; Isdahl, Nansubuga Nagadya; Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
TRestarting travel and tourism in the region must consider the entire ecosystem from aviation to small and medium sized enterprises and requires greater focus on health and safety. In this brief, expert informed recommendations for health focused interventions involve (i) strengthened management and planning, (ii) enhanced transmission barriers and sanitation, and (iii) well organized public health screening, all of which require the collaboration and coordination of governments, international organizations, relevant sectors, and stakeholders.
Keywords: Industry and state -- Asia; Economic policy -- Asia; Electronic book